Miss Holly is too jolly! - Gutman, Dan.; Paillot, Jim (New York, N.Y. : HarperTrophy, 2006)
Disaster reigns when A.J. participates in the school's holiday pageant celebrating Christmas, Hanukkah, and Kwanzaa.
Keywords: Schools -- Fiction; Holidays -- Fiction; Humorous stories